2004
DOI: 10.1111/j.0022-3816.2004.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Unemployment and Gubernatorial Popularity

Abstract: Considerable debate exists over whether the public holds the governor accountable for the state's economy. Part of the controversy stems from weak design and limitations in data, but part also from weakness in theory. We argue that voters recognize the limitations of state governments to affect the state economy and that they judge their governors on the state's unemployment situation relative to the unemployment situation of the national economy. To test this theory we use the Official State Job Approval Rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…The first is state unemployment, which we measure relative to national unemployment. Although studies have consistently found a negative effect of state unemployment levels on public assessments of the governor (Adams and Squire 2001;Barth and Ferguson 2002;Crew et al 2002;Hansen 1999aHansen , 1999b, we use the relative measure because the public has been shown both to distinguish between the national and state economies (Niemi, Bremer, and Heel 1999) and to hold the governor accountable for the relative health of the state economy in comparison to the national economy (Cohen and King 2004). Understanding that state and national unemployment rates are highly correlated, the people judge their governor's job performance using national economic conditions as a benchmark.…”
Section: State Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is state unemployment, which we measure relative to national unemployment. Although studies have consistently found a negative effect of state unemployment levels on public assessments of the governor (Adams and Squire 2001;Barth and Ferguson 2002;Crew et al 2002;Hansen 1999aHansen , 1999b, we use the relative measure because the public has been shown both to distinguish between the national and state economies (Niemi, Bremer, and Heel 1999) and to hold the governor accountable for the relative health of the state economy in comparison to the national economy (Cohen and King 2004). Understanding that state and national unemployment rates are highly correlated, the people judge their governor's job performance using national economic conditions as a benchmark.…”
Section: State Factorsmentioning
confidence: 99%
“…Understanding that state and national unemployment rates are highly correlated, the people judge their governor's job performance using national economic conditions as a benchmark. The governor's popularity declines when state unemployment exceeds national unemployment and rises under the opposite condition (Cohen and King 2004). Therefore, we measure state unemployment as the state unemployment rate minus the national unemployment rate, both lagged one month.…”
Section: State Factorsmentioning
confidence: 99%
“…2 Cohen and King (2004) find that when the state unemployment is lower than the national average, governors lose political capital and face worse approval ratings. Approval ratings are important not only because they are a key indication of re-election prospects (King 2001) but also because they expand the executive's ability to set their own policy agenda (Canes-Wrone and De Marchi 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given that "pocketbook" voters (i.e., voters who base their voting choices on their own economic situation) and "sociotropic" voters (i.e., voters who base their voting choices on national economic performance) both exist, one could speculate that voters could base their vote choices on state economic performance. Actually, Cohen and King (2004) have found that voters are able to differentiate unemployment rates on the state and national level, and they reward governors if state unemployment rate is lower than the national unemployment rate and hold governors accountable if it is higher. Garand and Ulrich (2008) demonstrate that individuals' sociotropic evaluations of the national economy are shaped, at least in part, by state economic performance.…”
Section: Political Effectsmentioning
confidence: 99%
“…Garand and Ulrich (2008) demonstrate that individuals' sociotropic evaluations of the national economy are shaped, at least in part, by state economic performance. Economic performance also influences popularity of governments and politicians (Cohen and King, 2004;Conover and Feldman, 1986;Garand and Ulrich, 2008;Mackuen, 1983;Nadeau et al, 1999).…”
Section: Political Effectsmentioning
confidence: 99%